Contribution of Leg Muscle Power and Height to High Jump Results - Iwan Fataha; Arief Ibnu Haryanto; Ardin Abdul Gani; Sulasikin Sahdi Kadir; Giofandi Samin; Gilang Ramadan (JUARA : Jurnal Olahraga, 2021)
This study aimed to determine the contribution of leg power and height to the straddle high jump. This research is correlational. This study's population was students of Sports Coaching Education at the Faculty of Sports and Health, Gorontalo State University semester 1 T / 2020-2021, which had a population of 43 students. The research sample is the entire population (total sampling). This study used a vertical jump test for leg muscle power and a Stadiometer for height measurement. The result, this study suggests that leg muscle power with height has a contribution to high jump results.